Teaching history through the use of multimedia (powerpoint) in selected schools in Saudi Arabia - Al-Qahtani, Mefleh Qublan (Institute of Education, International Islamic University Malaysia, 2013)
This experimental study aims to investigate the effects of both multimedia and direct teaching methods on the academic achievement and attitude of history students. This was carried out through teaching treatment group units of history subject using multimedia (PowerPoint) and teaching control group the same units through direct teaching. The study also explores the availability levels of instructional devices at secondary schools in the Asarah province, and the extent to which history secondary school teachers use these devices, including the possible difficulties and obstacles history teachers may encounter in using instructional devices. A mixed-method approach was used to collect and analyse the data. Survey questionnaires were administered to tenth grade history students to collect the quantitative data, whereas semi-structured interviews were conducted with history teachers. Descriptive analysis and ANOVA were used to analyse the quantitative data, and N-Vivo was used to analyse the qualitative data. The results revealed that the treatment group performed better compared to the control group on achievement and attitude scales. The analysis also found that instructional devices did exist in the sampled schools sampled. However, teachers seldom use these instructional devices due to a general sense of unfamiliarity, which results in a number of obstacles and difficulties. This causes history teachers to avoid the use of such technological teaching aids.